Exploratory Analysis Design and Development of Fantastic Fighting Scene For Promoting Indonesian Martial Arts - Muhammad Rizqiansyah Haqiqi Ali; Surya Tjahyadi (IJISTECH (International Journal of Information System and Technology), 2023)
This research aims to explore, analyze, and develop a fantastic fight scene to promote Indonesian martial arts. The purpose of this research is to introduce and promote Indonesian martial arts to the wider community by using available technology and media. The research method used in this study is the initial stage of research and development, followed by the ADDIE method in developing fantastic battle videos. The result of this research is a fantastic fighting video that showcases the skills and aesthetics of Indonesian martial arts. This video will present spectacular and mesmerizing actions that show the rich culture and traditions of Indonesian martial arts. This video will be published via the YouTube channel and is expected to be able to promote Indonesian martial arts to the wider community and provide an appreciation for the richness of Indonesian culture. This research is expected to contribute to the world of Indonesian martial arts and introduce Indonesian martial arts to the wider community.